The Balance of Intellectuality and Spirituality in Islamic Education: A Pedagogical Interpretation Study of QS Al-‘Alaq Verses 1-5 and QS Az-Zumar Verse 9 - Elsa Fikry Nurcahya; A ‘Izzatul Ifada; Sri Hafsari Fakriyah; Fatiha Nur Laili Azizah (Yayasan Insan Mulia Bima, 2024)
This study aims to explore the educational values contained in Surah Al-‘Alaq (verses 1–5) and Surah Az-Zumar (verse 9) using the tafsir tarbawi approach. This approach interprets Qur’anic verses by emphasizing educational values that are applicable and contextual, particularly in addressing the contemporary challenges of Islamic education. The research employs a qualitative method with a library research design, gathering data from the Qur’an, classical and contemporary exegesis (tafsir) sources, and relevant Islamic educational literature. The findings indicate that Surah Al-‘Alaq highlights the importance of scientific literacy rooted in tawhid (monotheism), while Surah Az-Zumar stresses that true knowledge is that which leads to khasyyah (reverent fear of God). These verses form a foundational framework for developing an Islamic education system that balances intellectual and spiritual aspects. The study is supported by the thoughts of scholars such as al-Ghazali and Syed Muhammad Naquib al-Attas, who emphasize the integration of knowledge, ethics, and adab (propriety). It is recommended that the tafsir tarbawi approach be strengthened in curriculum development, character education, and teacher training to shape insan kamil the ideal human being who embodies knowledge, faith, and noble character.